Does cold snare polypectomy completely resect the mucosal layer? A prospective single‐center observational trial. Issue 2 (10th September 2019) - Shichijo, Satoki; Takeuchi, Yoji; Kitamura, Masanori; Kono, Mitsuhiro; Shimamoto, Yusaku; Fukuda, Hiromu; Nakagawa, Kentaro; Ohmori, Masayasu; Arao, Masamichi; Iwatsubo, Taro; Iwagami, Hiroyoshi; Matsuno, Kenshi; et al.
Abstract: Background and Aim: The true incidence of incomplete muscularis mucosa resection with cold snare polypectomy (CSP) is unknown. We examined the incidence of incomplete muscularis mucosa resection both with and without cold snare defect protrusion (CSDP). Methods: We prospectively enrolled patients undergoing polypectomy for 4 to 9mm nonpedunculated polyps. We evaluated the presence of CSDP immediately following CSP and biopsied the CSDP or the center of the mucosal defect without CSDP. The presence of the muscularis mucosa and any residual polyp in the biopsies was evaluated histologically. The primary outcome was the incidence of incomplete mucosal layer resection defined as the presence of muscularis mucosa or residual polyp in the biopsies. Results: From August 2017 to October 2018, 188 patients were screened, and 357 polyps were included. CSDP was detected in 122/355 (34%) evaluated mucosal defects. Excluding five lesions requiring hemostasis immediately following CSP, 352 mucosal defects were biopsied. After excluding 102 biopsies containing normal mucosa, we evaluated 250 biopsies. The overall incidence of incomplete mucosal layer resection was 63% (159/250), 76% (68/90) with CSDP and 57% (91/159) without CSDP ( P  < 0.01). Both univariate and multivariate analyses showed that size (≥ 6 mm), resection time (≥ 5 s), and serrated lesions were risk factors for CSDP. Conclusions: Cold snare defect protrusion (CSDP), which was present with 36%, was a good indicator for incomplete mucosal layer resection. Even in nonCSDP polypectomies, 57% of the mucosal layer was not removed completely. Thus, CSP should be used for intra‐epithelial lesions only, and careful pretreatment evaluation is recommended.